Ethnobotany and mining heritage: The case of Aljustrel - Figueira, Ana Paula; Mendonça de Carvalho, Luis; Encarnação, Ana; Figueira, Victor; Fernandes, Francisca Maria (Ethnobotany Research and Applications, 2026)
Aljustrel is a mining town located in southern Portugal, within the Iberian Pyrite Belt and since the Antiquity the local geological resources have been exploited. As in most human communities, plants sustained the miners’ health, diet, and labor. Plants helped to address the hard conditions of mining life, because respiratory illnesses and wounds were very common and were treated with local medicinal plants. Besides healing, local flora was used in traditional soups and stews, providing nutrition. These practices revealed a deep interdependence between miners and plants who helped them in a demanding and harsh profession and were also seen as cultural elements of their community. In this study, miners and their families selected the plant species they considered most significant, both for their utilitarian functions and their cultural value, during periods of active labour and close engagement with the mining environment. Keywords: Miners and plants, Aljustrel, material culture, traditional knowledge, medicinal plants